Epidemiological Study of the Incidence of Demam Berdarah Dengue (DBD) in Kupang City in 2017-2019 - Alexia Gudelia Wowa; Honey I. Ndoen; Soleman Landi (Universitas Nusa Cendana, 2023)
Dengue Hemorrhagic Fever or abbreviated as DHF is an infection caused by the dengue virus which is transmitted by the Aedes aegypti mosquito. Kupang city is one of the areas with a high number of dengue cases every year. DHF cases that occurred in Kupang City from 2017-2019 continued to increase. In 2017 there were 132 cases, in 2018 there were 238 cases, in 2019 it increased to 650 cases. The presentation of information in the form of mapping can provide the right solution to help overcome problems regarding DHF in Kupang City. The purpose of the study was to conduct an epidemiological study of the incidence of DHF through mapping techniques in Kupang City in 2017-2019 based on people, time and place. The type of research used is descriptive epidemiological research. The sample in this study were all cases of DHF in 2017-2019. The results of the study, the distribution of dengue cases based on age, the highest cases occurred in the age group 1-4 years and male sex became the highest case during 2017-2019. There was an increase in cases every month and the peak was in January. The cause of the high cases of DHF is a factor of population density, rainfall, and air humidity. There needs to be cooperation from all parties, both the government and the community in the context of dealing with dengue case.